IDENTIFIKASI JENIS-JENIS BURUNG AIR DI KAWASAN MANGROVE DESA TANJUNG SALEH KECAMATAN KAKAP KABUPATEN KUBU RAYA - Irmawan, Agustinus; Nurdjali, Bachrun; Siahaan, Sarma (JURNAL HUTAN LESTARI, 2014)
The purpose of the study was to determine the types of water birds found in mangrove forests the village of Tanjung Saleh District snapper Kubu Raya district. This study is expected to provide information and data on water bird species identification in the mangrove forest the village of Tanjung Saleh District snapper Kubu Raya regency, so it can be used as a programming effort management, protection and conservation in the region. The results of research on the muddy shore habitats found 17 species from 10 families. The types of the most dominant family Scolopacidae is Temminck’ Stint (Calidris temminckii), Common Redshank (Tringa totanus), Commmon Greenshank (Tringa nebularia) and Green Sandpipers (Tringa ochropus). The results of research on coastal mangrove habitat types found 8 species from 5 different families. The types of family Accipitridae, Ardeidae and Alcedinidae most predominantly found each of the 2 types of water birds are Brahminy Kite (Haliastur indus), Black Eared Kite (Milvus migrans), Chinese Egret (Egretta eulophotes), Little Heron (Butorides striata), Stork Billed Kingfisher (Pelargopsis capensi) and Collared Kingfisher (Todirhamphus chloris). The research found 12 species of water birds, including the protected status based (Department of Forestry, 1990), namely, the White Bellied Sea Eagle (Haliaeetus leucogaster), Black Shouldered Kite (Elanus caeruleus), Little Egret (Egretta garzetta), Oriental Darter (Anhinga melanogaster), Lesser Adjutant (Leptoptilos javanicus), White Winged Tern (Chlidonias leucopterus), Whiskered Tern (Chlidonias hbryda), Brahminy Kite (Haliastur indus), Black Eared Kite (Milvus migrans), Chinese Egret (Egretta eulophotes), Stork Billed Kingfisher (Pelargopsis capensi) and Collared Kingfisher (Todirhamphus chloris). Keyword : Water bird, identification, mangrove area